Macrophage inhibitory cytokine‐1/growth differentiation factor‐15 as a predictor of colonic neoplasia. Issue 3 (1st June 2017) - Danta, M.; Barber, D. A.; Zhang, H. P.; Lee‐Ng, M.; Baumgart, S. W. L.; Tsai, V. W. W.; Husaini, Y.; Saxena, M.; Marquis, C. P.; Errington, W.; Kerr, S.; Breit, S. N.; et al.
Summary: Background: Serum macrophage inhibitory cytokine‐1 (MIC‐1/GDF15) concentration has been associated with colonic adenomas and carcinoma. Aims: To determine whether circulating MIC‐1/GDF15 serum concentrations are higher in the presence of adenomas and whether the level decreases after excision. Methods: Patients were recruited prospectively from a single centre and stratified into five groups: no polyps (NP); hyperplastic polyps (HP); sessile serrated ademona (SSA); adenomas (AP); and colorectal carcinoma (CRC). Blood samples were collected immediately before and 4 weeks after colonoscopy. MIC‐1/GDF15 serum levels were quantified using ELISA. Results: Participants (n=301) were stratified as: NP; n=116 (52%), HP; n=37 (12%), SSA; n=19 (7%), AP; n=68 (23%); and CRC; n=3 (1%). Patients were excluded from the study due to nondiagnostic pathology (n=9, 3%) and exclusion criteria (n=20, 6%). In the 272 remaining subjects (M=149; F=123), age ( P =.005), history of colonic polyps ( P =.003) and family history of colonic polyps ( P =.002) were associated with presence of adenomas. Baseline median MIC‐1/GDF15 serum levels increased significantly from NP 609 (460‐797) pg/mL, HP 582 (466‐852) pg/mL, SSA 561 (446‐837) pg/mL to AP 723 (602‐1122) pg/mL and CRC 1107 (897‐1107) pg/mL; ( P <.001). In the pre‐ and postpolypectomy paired adenoma samples median MIC‐1/GDF15 reduced significantly from 722 (603‐1164) pg/mL to 685 (561‐944) pg/mL ( P =.002). A ROC analysis for serum MIC‐1/GDF15 to identify adenomatous polyps indicated an area under the curve of 0.71. Conclusions: Our data suggest that serum MIC‐1/GDF15 has the diagnostic characteristics to increase the detection of colonic neoplasia and improve screening.